2015
DOI: 10.1177/1478210315572675
|View full text |Cite
|
Sign up to set email alerts
|

Neo-liberal educational reform and the role of teachers’ unions in the context of private schools in Nepal: Possibility or paralysis?

Abstract: Nepal experienced political change from absolute monarchy to constitutional monarchy in 1990 and finally to a republic in 2008. These changes in the political climate were followed by subsequent change in the educational policy as the incoming regimes tried to incorporate its ideology in the educational policy. This paper analyses the role of teachers’ unions in the educational reform in Nepal since the 1990s with special focus on private schooling context. This paper draws information collected through qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…This study revealed that the school education system, teaching profession, and procedure to form SMC must be free from politics, supporting Shrestha's findings (2005) and Brinkmann's (2018) findings. The findings are also consistent with Poudel's (2015) report, which found that teachers' unions in Nepal were not working for teachers' welfare. Similarly, this study revealed that the SMC did not treat teachers fairly and equally.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study revealed that the school education system, teaching profession, and procedure to form SMC must be free from politics, supporting Shrestha's findings (2005) and Brinkmann's (2018) findings. The findings are also consistent with Poudel's (2015) report, which found that teachers' unions in Nepal were not working for teachers' welfare. Similarly, this study revealed that the SMC did not treat teachers fairly and equally.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, the relationship between the SMC and teachers, in general, was very poor and tense, and SMCs were being politicized by political parties (Shrestha, 2005). Similarly, Poudel (2015) reported that various teachers' unions are associated with political parties and carry their political parties' ideologies rather than working for the benefits and welfare of Nepalese teachers. Therefore, this study sought to examine the factors affecting high school mathematics teachers' job satisfaction, important factors affecting teachers' professional growth, and teachers' impressions of the school environment.…”
Section: Schools In Nepalese Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The Nepali Congress is a liberal political party that dominated the political scene of Nepal soon after Nepal became a democratic country in the early 1990s. It is a good example of neoliberalism and privatisation of education in Nepal (Sharma Poudyal, 2013a, 2015). However, with the Maoists becoming a dominant political force, private schools of Nepal came under constant attack (Act governing private schools sought, 2010; Don’t commercialise education, 2010; Thapa, 2011).…”
Section: Introductionmentioning
confidence: 99%